Factors affecting employee retention in a South African bank . - Rammutla, Kwena Ludwig (My University, 2014)
ABSTRACT The concept of “war for talent” is neither new nor does it only affect the international economies (Beechler & Woodward, 2009). This phenomenon has become Human Resources (HR) professionals’ contemporary “mantra” in the corporate setting and it will prevail for the future and substantial upcoming ages (O’Callaghan, 2008; Mehta, 2011). The aim of this study was to identify key retention factors that affect employees’ decision to remain employed in an organisation. Utilising the questionnaire-based survey which was published on Qualtrics, the data was collected from 246 business banking division of a bank in South Africa. In order to achieve the results, the data has undergone numerous statistical analyses, including regression analysis. Key factors which were identified affecting employees’ decision to remain employed in a South African bank were skills and talent development and autonomy. In the continuing quest to retain top talented employees, the employers should consider offering their skilled workforce freedom to plan and execute work independently, flexible working hours within limits, ability to influence the kind of work that gets assigned to employees, the opportunity to do what employees do best every day, opportunities to develop new skills and knowledge and to use these in challenging and interesting ways, training and skills improvement should be actively encouraged within a wide range of internal training programmes.
MBA 2014
Keywords: Employee retention,Banks and banking.